Rabies Disease and Prophylaxis Knowledge Among Turkish Medical Students: Insights from a Cross-Sectional Study - Vasfiye Demir Pervane; Pakize Gamze Erten Bucaktepe; Fatma Meral İnce; Dicle Demir; Simanur Koç (Tropical Medicine and Infectious Disease)
Rabies is a fatal infectious disease that can be prevented with vaccination. The aim of this study was to evaluate the level of rabies knowledge among medical faculty students. This cross-sectional study included students in the medical faculty of a university hospital. The level of rabies knowledge was evaluated with a questionnaire evaluating 70 parameters. A total of 892 students participated in this study. Medical students knew that dogs and cats transmit rabies at high rates (96.9% and 87.4%, respectively) but understood less about other animals. Pregnancy (45.2%), being >65 years of age, having a chronic disease, and being immunosuppressed were indications for rabies vaccine, with rates between 31.4 and 37.4%. In total, 64.3% of respondents stated that the nearest health center should be approached to seek medical care, without first touching the wound. While indications for vaccination were correctly reported to be high after bites or scratches (74.2–94.6%), such indications were considered to be lower for other types of contact (46.2–66.6%). Indications for rabies immunoglobulin administration were correctly recognized at rates between 15.9% and 57.8%. Overall, the mean rabies knowledge level was 41.82 (Max. score 70). There was a statistically significant relationship between the total and subgroup rabies knowledge scores and class level, having taken a rabies course, a history of dog bites among the respondents or their family members, and possessing information about rabies. It was determined that the rabies knowledge levels among the students were insufficient. Having received lessons about rabies or a history of being bitten by an animal with suspected rabies were found to be important factors for increased knowledge about rabies.